Why are Urban Formal Sector Wages in LDCs above the Market-Clearing Level? - Vibhooti Shukla; Oded Stark (Harvard University, Center for Population Studies Cambridge, 1989)
In this paper we link urban labor market dualism and the fixity of formal sector wages in expected income migration models with urban agglomeration economies. A possible productivity- efficiency rationale for the "institutional" wage is identified and explored. In addition, a rationalization for the informal sector is suggested in this context. We propose a motivation for determinating high urban wages as part of a choice-theoretic behavioral framework, perform illustrative simulations of factors influencing an equilibrium urban wage premium, and point out directions for further research delineated by our analytical propositions.
Keywords: 330